A literature review of ERP system, challenges and opportunities of ERP implementation on organization - Tiên, Nguyễn Thủy; Tâm, Trương Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
A for-profit organization believes that ERP (enterprise resource planning) system effectiveness can be achieved through long-term rather than short-term processes. Moreover, some large corporations benefit more than others from the use of ERP software. As a result, the ERP system is now live. This study aims to demonstrate the numerous benefits of effective ERP system implementation from the organization’s infancy to maturity. In addition, the researcher and analyst investigate the ERP system’s application in numerous businesses by analyzing and reviewing previous academic journals and research. This research employs a semi-systematic literature review as its methodology. In this research paper, the fundamental concept of the ERP system and its organizational benefits are discussed. From a review of the relevant literature, this study discusses the aforementioned statement using case studies to demonstrate the ERP experiences of various companies. This research also reveals that implementing the ERP system is regarded as one of the most challenging projects that require collaboration between ERP project members. Theoretically, there is no end date for ERP implementation, particularly after the system has been established and implemented.